Revitalizing the medina of Tunis as a national symbol - Escher, Anton; Schepers, Marianne (ERDKUNDE, 2008)
Many Arab old towns in Maghreb and in South West Asia have been gripped by a fundamental and dynamic urban renewal during the 20th century. While the renewal process in most old towns can be attributed to global dynamics, the actors involved in the old town of Tunis are almost exclusively from a local and national level. This paper aims to highlight the processes and strategies for revitalizing the old town of Tunis, to analyse its motives and explain why the renewal process is spurred by local interest instead of global dynamics. For instance, the medina serves primarily as a national symbol. The symbolic significance of the old town of Tunis in terms of establishing identity coincides with the strategies of a state-funded revitalization process and increasing efforts to showcase the old town.